2015
DOI: 10.1007/8904_2015_483
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Plasma Globotriaosylsphingosine Levels After Switching from Agalsidase Alfa to Agalsidase Beta as Enzyme Replacement Therapy for Fabry Disease

Abstract: Introduction: Agalsidase alfa and agalsidase beta, recombinant enzyme preparations for treatment of Fabry disease (FD), have different approved dosing schedules: 0.2 mg/kg and 1.0 mg/kg every other week (EOW), respectively.Methods: This open-label, multicenter, exploratory phase 4 study evaluated plasma globotriaosylsphingosine (lyso-GL-3) and plasma and urine globotriaosylceramide (GL-3) levels at baseline and 2, 4, and 6 months after the switch from agalsidase alfa (0.2 mg/kg EOW for !12 months) to agalsidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 53 publications
(71 reference statements)
0
24
2
Order By: Relevance
“…Plasma Gb3 is elevated in patients with Fabry disease and has been demonstrated to be reduced by treatment with ERT . A decrease in plasma GlcCer, LacCer, Gb3, and urine Gb3 was observed, demonstrating that lucerastat 1,000 mg b.i.d.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Plasma Gb3 is elevated in patients with Fabry disease and has been demonstrated to be reduced by treatment with ERT . A decrease in plasma GlcCer, LacCer, Gb3, and urine Gb3 was observed, demonstrating that lucerastat 1,000 mg b.i.d.…”
Section: Discussionmentioning
confidence: 90%
“…Neither ERT nor miglustat conclusively improved renal and cardiac function in randomized Plasma Gb3 is elevated in patients with Fabry disease and has been demonstrated to be reduced by treatment with ERT. 45 A decrease in plasma GlcCer, LacCer, Gb3, and urine Gb3 was observed, demonstrating that lucerastat 1,000 mg b.i.d. inhibits GCS and provides a-GalA substrate reduction with a fast onset.…”
Section: Discussionmentioning
confidence: 92%
“…Multivariate linear regression analysis showed that LysoGb3 levels were independently associated with, serum creatinine (β=0.09, 95%CI 0.04-0.13, P<0.001) and the presence of cardiomyopathy (β=25, 95%CI 9.8-41, P=0.002). LysoGb3 levels were higher in males with frame-shift and nonsense mutations than in males with missense mutations (84 [72-109] vs 41 [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]ng/ml, P=0.002).…”
Section: Resultsmentioning
confidence: 99%
“…Failure to reduce plasma lyso-GL-3 levels to (near-)normal levels may be an indication to intensify ERT and evaluate anti-drug IgG antibodies [17]. No timeframe for monitoring the lyso-GL-3 response to ERT has been included at this time and needs further research.…”
Section: Plasma Lyso-gl-3mentioning
confidence: 99%